2022
DOI: 10.1371/journal.pntd.0010233
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestations of Rift Valley fever in humans: Systematic review and meta-analysis

Abstract: Background Rift Valley fever (RVF) is an emerging, neglected, mosquito-borne viral zoonosis associated with significant morbidity, mortality and expanding geographical scope. The clinical signs and symptoms in humans are non-specific and case definitions vary. We reviewed and analysed the clinical manifestations of RVF in humans. Methods In this systematic review and meta-analysis we searched on different dates, the Embase (from 1947 to 13th October 2019), Medline (1946 to 14th October 2019), Global Health (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
21
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(24 citation statements)
references
References 84 publications
2
21
1
Order By: Relevance
“…This finding was consistent with another report based on pathological evaluation of post-mortem and necropsy tissue samples from animals and humans clinically suspected of having RVFV infection during the 2006-2007 outbreak in Eastern Africa (Breiman et al, 2010). In this review, relatively high estimates of the RVF CFR in humans (27.5%) during outbreak periods were consistent with previous study among confirmed cases (Anywaine et al, 2022). This high RVF CFR could be explained by the fact that during outbreaks, epidemiological investigations focus primarily on the identification of severe cases in epidemiological settings where all RVF cases are hard to trace.…”
Section: Discussionsupporting
confidence: 93%
“…This finding was consistent with another report based on pathological evaluation of post-mortem and necropsy tissue samples from animals and humans clinically suspected of having RVFV infection during the 2006-2007 outbreak in Eastern Africa (Breiman et al, 2010). In this review, relatively high estimates of the RVF CFR in humans (27.5%) during outbreak periods were consistent with previous study among confirmed cases (Anywaine et al, 2022). This high RVF CFR could be explained by the fact that during outbreaks, epidemiological investigations focus primarily on the identification of severe cases in epidemiological settings where all RVF cases are hard to trace.…”
Section: Discussionsupporting
confidence: 93%
“…24,[33][34][35] Alternatively, this difference in the clinical manifestation of RVF infection could be attributed to variation in the virus strains of some clades of viruses are more associated with severe clinical presentations of the disease. [36][37][38] A similar situation has been observed during the currently ongoing Mpox outbreak of global concern. 39 Clade IIb of the Mpox virus that diverged from the West African lineage is associated with globally expanded transmission outside the endemic areas with none severe clinical presentation.…”
Section: Discussionsupporting
confidence: 68%
“…Recently, there is growing evidence about disease emergence and unusual presentation of endemic diseases 24,33–35 . Alternatively, this difference in the clinical manifestation of RVF infection could be attributed to variation in the virus strains of some clades of viruses are more associated with severe clinical presentations of the disease 36–38 . A similar situation has been observed during the currently ongoing Mpox outbreak of global concern 39 .…”
Section: Discussionmentioning
confidence: 83%
“…Transmission occurs via contact with blood or organs of infected animals (typically cattle) or via mosquito bite. Following an incubation period of 2-6 days, a diverse array of systemic presentations of RVF can occur (65). The classical presentation is that of a generalized febrile/flu-like illness with hepatic syndrome (elevated liver enzymes, hepatosplenomegaly, liver failure).…”
Section: Phenuiviridae Rift Valley Fevermentioning
confidence: 99%